Method for preparing nano barium titanate powder by two-stage hydrolysis

CN122916655APending Publication Date: 2026-10-16LUOYANG JINGLIAN OPTOELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216883.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,固相法存在明显的技术缺陷:由于固相反应依赖于原料颗粒间的扩散传质,高温煅烧过程中晶粒容易粗化,产物粒径通常粗大(0.8~1.0μm以上);颗粒间因表面能较高而发生硬团聚,导致团聚严重、粒径分布宽泛;此外,为满足粒度要求进行的二次球磨过程容易引入杂质,使粉体纯度下降

Benefits of technology

(1)本发明采用两段水解法,创新性地替代了传统固相法、液相沉淀法或直接水解法等工艺。在第一水解阶段,控制较低温度(35~40℃)使钛源缓慢水解,形成稳定的金属羟基络合物,得到具有蓝色胶状特征的第一水解产物。此时钛酸四乙酯的水解速率被有效抑制,确保水解过程平稳进行。在第二水解阶段,加入水解剂-乙醇溶液后升温至80~90℃,使水解剂原位水解产生沉淀剂(如草酸、硫酸或碳酸/二氧化碳等),所述沉淀剂与体系中均匀分散的钡离子和钛离子同步发生络合沉淀反应。两段水解的核心优势在于:将钛源的水解过程与水解剂的水解过程在时间上分离。如果钛源和水解剂同时水解,则钛源水解产生的胶体与沉淀反应同时发生,两种反应的相互干扰将导致成核速率不可控、颗粒尺寸不均;而分步进行则可使钛源先在优化的条件下形成稳定的羟基络合物,待体系均匀化后再引入水解剂进行原位水解和沉淀,从而真正实现反应体系内各位置同步、均匀成核与生长,有效避免了传统工艺中因局部浓度梯度导致的颗粒团聚及粒径分布不均问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916655A_ABST
    Figure CN122916655A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing nano barium titanate powder by two-stage hydrolysis, which comprises the following steps: dissolving a barium source and a rare earth salt in a pure water-ethanol mixed solvent, adjusting the pH to 1.5-2.0, adding a titanium source-ethanol solution dropwise under ice water bath conditions to obtain a precursor mixed solution; performing ultrasonic-assisted hydrolysis at 35-40 DEG C for 2-3 hours in a first hydrolysis stage; adding a hydrolysis agent-ethanol solution in a second hydrolysis stage, and performing incubation at 80-90 DEG C for 4-8 hours, so that the hydrolysis agent is hydrolyzed in situ to generate a precipitant and is combined with titanium ions and barium ions to precipitate; and then performing washing until the conductivity is less than or equal to 50 muS / cm, performing spray drying, performing three-stage calcination, and performing sieving, so that the nano barium titanate powder is obtained. By means of two-stage hydrolysis, uniform nucleation and growth are realized, ultrasonic-assisted dispersion and a three-stage calcination process are combined, the average particle size of the prepared barium titanate powder is less than or equal to 100 nm, the particle size distribution is narrow, and the rare earth elements are uniformly distributed at an atomic level, so that the prepared barium titanate powder can meet the strict requirements of high-end MLCCs on dielectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of barium titanate powder preparation, specifically a method for preparing nano-barium titanate powder using a two-stage hydrolysis process. Background Technology

[0002] Barium titanate (BaTiO3) is a strong dielectric material with a perovskite structure. Due to its high dielectric constant, low loss, and excellent ferroelectric and piezoelectric properties, it has become the core dielectric material for multilayer ceramic capacitors (MLCCs) and is hailed as the "pillar of the electronic ceramics industry." The particle size, dispersibility, and crystal integrity of barium titanate powder directly determine the dielectric performance and reliability of MLCCs. With the rapid development of industries such as consumer electronics, new energy vehicles, and 5G communications, MLCCs are evolving towards miniaturization, higher capacitance, and thinner layers. The dielectric layer thickness has been reduced to below 1 μm, requiring barium titanate powder with an average particle size D50 ≤ 100 nm, narrow particle size distribution, excellent dispersibility, and extremely low impurities. However, China has long relied on imports for high-end powders, making it difficult to meet the demand for domestic substitution. Therefore, developing new methods for preparing high-purity, ultrafine, uniformly distributed, and well-dispersed barium titanate powder has significant industrial value.

[0003] Currently, the main preparation methods for barium titanate powder fall into two categories: solid-phase method and liquid-phase method.

[0004] The solid-state method uses barium carbonate and titanium dioxide as raw materials, which are calcined at 1250–1300℃ to produce a solid-state reaction. This method is simple, low-cost, and can be mass-produced, making it the main method for industrial production. However, the solid-state method has significant technical drawbacks: because the solid-state reaction depends on diffusion and mass transfer between raw material particles, the grains tend to coarsen during high-temperature calcination, resulting in large product particle sizes (above 0.8–1.0 μm); the high surface energy between particles leads to hard agglomeration, resulting in severe agglomeration and a wide particle size distribution; furthermore, the secondary ball milling process to meet particle size requirements easily introduces impurities, reducing powder purity. These drawbacks mean that solid-state method products can only meet the needs of low- to mid-range devices. As the dielectric layer thickness of MLCCs decreases to below 1 μm, the particle size and dispersibility of solid-state method powders can no longer meet the stringent requirements of high-end MLCCs.

[0005] Liquid-phase methods mainly include coprecipitation, sol-gel, and hydrothermal methods. While these methods can achieve the preparation of powders with small particle sizes, each has its own inherent drawbacks. Coprecipitation involves directly adding a precipitant (such as oxalic acid or carbonate) to a solution containing barium and titanium salts, causing barium and titanium ions to precipitate simultaneously. Although relatively simple to operate, this method suffers from the following problems: First, the barium-titanium ratio is difficult to control precisely due to the difference in precipitation rates between barium and titanium salts in aqueous solution; second, the nucleation rate is extremely fast during direct precipitation, causing particles to rapidly agglomerate and grow in solution, encapsulating a large amount of impurities and unreacted raw material ions, leading to complex washing processes and raw material waste; third, the encapsulated impurities are difficult to remove during calcination, and the product is prone to agglomeration. The sol-gel method, based on the hydrolysis and polymerization of metal alkoxides, can achieve uniform mixing at the molecular level, but suffers from high raw material costs, difficulty in process control, and a tendency for product agglomeration. The hydrothermal method involves reactions under high temperature and high pressure conditions, resulting in well-developed crystals and less agglomeration in the product. However, it requires demanding equipment, involves large investments, and is prone to barium vacancies, making industrialization difficult.

[0006] In summary, existing preparation methods struggle to achieve an ideal balance between particle size control, dispersibility, cost, and production efficiency. How to achieve controllable preparation of barium titanate powder with nanoscale particle size, narrow distribution, and high dispersibility without increasing equipment complexity and production costs is a pressing technical challenge in this field. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a two-stage hydrolysis method for preparing nano-barium titanate powder. This method achieves atomic-level uniform distribution of rare earth ions by precisely controlling the hydrolysis process in stages, combined with ultrasonic-assisted dispersion and a three-stage calcination process, resulting in barium titanate powder with an average particle size ≤100nm and uniform distribution.

[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A method for preparing barium titanate nanoparticles via a two-stage hydrolysis process includes the following steps: S1. Ingredients: Add pure water and anhydrous ethanol to the reaction vessel, stir and mix at low speed, then add barium source and soluble rare earth salt, continue stirring at low speed until completely dissolved, then add hydrochloric acid to adjust the pH of the solution to 1.5~2.0; place the reaction vessel in an ice-water bath to control the solution temperature to less than 10℃, increase the stirring speed to medium speed, slowly add titanium source-ethanol solution to the solution, stir evenly to obtain precursor mixture; S2, First hydrolysis stage: Reduce the stirring speed to low speed, apply ultrasonic treatment to the precursor mixture and heat to 35~40℃, keep warm for 2~3 hours to fully hydrolyze the titanium source and obtain the first hydrolysis product. S3. Second hydrolysis stage: While maintaining low-speed stirring and ultrasonic treatment, slowly add hydrolyzing agent-ethanol solution to the first hydrolysis product, then raise the temperature to 80~90℃ and keep it at that temperature for 4~8 hours to hydrolyze the hydrolyzing agent to generate a precipitant. The precipitant undergoes a complexation precipitation reaction with titanium ions and barium ions in the solution to obtain the second hydrolysis product. S4. Washing: After concentrating the second hydrolysis product, wash it through a circulating filtration device to remove residual soluble impurities until the conductivity of the filtrate is ≤50μS / cm. S5. Spray drying: The washed product is spray dried to obtain intermediate powder; S6. Calcination and sieving: The intermediate powder is placed in a calcination furnace for three-stage calcination. After cooling, the calcined powder is broken up and sieved to obtain nano barium titanate powder.

[0009] Furthermore, in step S1, the barium source is barium chloride; The titanium source is tetraethyl titanate, and the concentration of the titanium source in the titanium source-ethanol solution is 5-10 wt%. The soluble rare earth salt is one or more of yttrium salt, dysprosium salt, and holmium salt. The amount of a single rare earth salt added is 0.2 to 1 mol of the titanium source material, and the total amount of rare earth salt added is 0.5 to 2 mol of the titanium source material.

[0010] Furthermore, in steps S2 and S3, the frequency of the ultrasonic treatment is 20~40kHz; In step S2, stop stirring after heating to 35~40℃, and turn on medium speed stirring for 1~5 minutes every 1~2 hours during the heat preservation process; In step S3, maintain low-speed stirring throughout the heat preservation process.

[0011] Further, in step S3, the hydrolysant is selected from any one of dimethyl sulfate, diethyl sulfate, dimethyl oxalate, dibutyl oxalate, and urea, and the concentration of the hydrolysant in the hydrolysant-ethanol solution is 20~30wt%.

[0012] Furthermore, in step S4, the filter membrane used in the circulating filtration device is selected from any one of honeycomb tubular ceramic filter membrane, disc rotating ceramic filter membrane, and flat plate ceramic filter membrane; Before washing, the second hydrolysis product is concentrated to a solid content of 25±5% before washing.

[0013] Furthermore, in step S6, the specific operation of the three-stage calcination is as follows: Low-temperature calcination: Increase the temperature to 400-500℃ at a rate of 0.2-0.5℃ / min and hold for 6-8 hours; Medium-temperature calcination: Increase the temperature to 600-700℃ at a rate of 0.2-0.5℃ / min and hold for at least 6 hours; High-temperature calcination: Increase the temperature to 900-1100℃ at a rate of 3-5℃ / min and hold for 1 hour.

[0014] Furthermore, in step S6, the calcining furnace is any one of a lifting calcining furnace, a box-type calcining furnace, a tunnel-type calcining kiln, or a tube furnace; the calcining container is any one of a corundum crucible, a zirconia crucible, or a mullite crucible.

[0015] Furthermore, in step S6, the dispersing and sieving are carried out using an air jet mill in conjunction with a 300-mesh vibrating screen.

[0016] Furthermore, in step S5, the inlet air temperature of the spray dryer is 180~200℃, and the outlet air temperature is 80~90℃.

[0017] Furthermore, the average particle size D50 of the obtained barium titanate nanoparticles is ≤100nm.

[0018] Beneficial effects Compared with the prior art, the present invention has the following advantages: (1) This invention employs a two-stage hydrolysis method, innovatively replacing traditional solid-phase methods, liquid-phase precipitation methods, or direct hydrolysis methods. In the first hydrolysis stage, a relatively low temperature (35-40℃) is controlled to allow the titanium source to hydrolyze slowly, forming a stable metal hydroxyl complex, resulting in a first hydrolysis product with a blue colloidal characteristic. At this time, the hydrolysis rate of tetraethyl titanate is effectively suppressed, ensuring a stable hydrolysis process. In the second hydrolysis stage, after adding a hydrolyzing agent-ethanol solution, the temperature is raised to 80-90℃, causing the hydrolyzing agent to hydrolyze in situ to produce a precipitant (such as oxalic acid, sulfuric acid, or carbonic acid / carbon dioxide, etc.). The precipitant undergoes a complexation precipitation reaction simultaneously with the uniformly dispersed barium and titanium ions in the system. The core advantage of the two-stage hydrolysis is that it separates the hydrolysis process of the titanium source from the hydrolyzing process of the hydrolyzing agent in time. If the titanium source and the hydrolysant are hydrolyzed simultaneously, the colloids and precipitation reactions generated by the titanium source hydrolysis will occur simultaneously. The mutual interference of the two reactions will lead to uncontrollable nucleation rate and uneven particle size. However, the stepwise process allows the titanium source to first form a stable hydroxyl complex under optimized conditions. After the system is homogenized, the hydrolysant is introduced for in-situ hydrolysis and precipitation, thereby truly achieving synchronous and uniform nucleation and growth at all locations in the reaction system. This effectively avoids the problems of particle agglomeration and uneven particle size distribution caused by local concentration gradients in traditional processes.

[0019] (2) This invention uses organic esters or urea as the key hydrolysing agent in the second stage of hydrolysis, replacing the traditional method of directly adding precipitants (such as oxalic acid, sulfates, or carbonates). When precipitants are added directly, a rapid precipitation reaction occurs instantly upon contact with barium and titanium ions in the solution. Due to the extremely high local supersaturation, the nucleation rate is fast and uneven, easily forming particles of varying sizes that encapsulate impurities. In contrast, this invention uses a hydrolysing agent slowly added to the reaction system in the form of an ethanol solution, which is then hydrolyzed in situ at 80–90°C to produce precipitant molecules. For example, dimethyl oxalate hydrolyzes to produce oxalic acid; diethyl sulfate hydrolyzes to produce sulfuric acid; and urea hydrolyzes to produce carbonic acid / carbon dioxide and ammonia. This in-situ hydrolysis method controls the precipitant formation rate to the hydrolysis rate of the hydrolysing agent, thereby achieving uniform release of precipitant molecules in the reaction system, truly realizing multi-point synchronous hydrolysis-complexation-precipitation, significantly reducing the precipitation rate, and promoting uniform particle growth. Meanwhile, this system significantly improves the fluidity and uniformity of the slurry, ensuring the uniform co-precipitation of barium ions, titanium ions, and other rare earth metal ions at the microscale, and guaranteeing the consistency of the stoichiometric ratio. Among these, dimethyl oxalate is the most effective hydrolysate, as the barium oxalate precursor formed by oxalic acid with barium and titanium ions has a defined chemical composition and good thermal decomposition characteristics, which is beneficial for obtaining high-purity, ultrafine barium titanate powder.

[0020] (3) This invention introduces ultrasonic-assisted treatment (frequency 20-40kHz) during the hydrolysis process. When ultrasound propagates in the liquid medium, it generates a cavitation effect—a large number of micro-cavitation bubbles are formed in the liquid. These cavitation bubbles collapse when the sound pressure reaches a certain value, generating local high temperature and high pressure, as well as strong shock waves and micro-jets. This effect plays multiple roles in the reaction system: firstly, the strong shear force and shock waves generated by the cavitation effect can effectively break up the soft agglomeration between particles; secondly, the mechanical stirring effect of ultrasound strengthens the mass transfer process of the reaction system, making the reactant concentration field more uniform; thirdly, ultrasonic cavitation promotes the uniform mixing of rare earth ions and metal ions at the molecular level. Through the synergistic effect of the above, the soft agglomeration of particles is effectively suppressed, ensuring the monodispersity of nanoparticles, while improving the doping uniformity of rare earth elements.

[0021] (4) This invention employs a three-stage calcination process, completing different physicochemical transformations in three stages: low temperature, medium temperature, and high temperature. The low temperature stage (400–500°C) mainly removes residual Cl. -The process involves three stages: ion removal (derived from hydrochloric acid and barium chloride) and decomposition of some organic residues; removal of residual carbon from the intermediate powder in the intermediate temperature stage (600–700℃), leading to the gradual decomposition of the barium oxalate precursor; and solid-state reaction of Ba and Ti in the high temperature stage (900–1100℃) to generate barium titanate with a perovskite structure. Compared to traditional one-step or two-stage calcination, this invention features finer temperature stages and more precise temperature control. The low and medium temperature stages employ slow heating (0.2–0.5℃ / min) to ensure impurities are fully volatilized and not encapsulated by residues; the high temperature stage involves rapid heating (3–5℃ / min) to shorten the high-temperature residence time and inhibit excessive grain growth. This three-stage calcination process more accurately and effectively removes various residual impurities from the powder, obtaining high-quality nano-barium titanate powder while maintaining powder purity.

[0022] (5) This invention achieves uniform molecular-level dispersion of rare earth ions at the solution level by dissolving soluble rare earth salts (yttrium salts, dysprosium salts, holmium salts, etc.) together with the barium source in a pure water-ethanol mixed solvent during the batching stage. Subsequently, through two stages of hydrolysis and complexation precipitation, rare earth ions co-precipitate with barium and titanium ions at the atomic scale, ensuring atomic-level uniform distribution of rare earth elements in the final barium titanate powder. The amount of a single rare earth salt added is 0.2–1 mol% of the amount of titanium source, and the total amount of rare earth salt added is 0.5–2 mol% of the amount of titanium source, which enables precise control of the dielectric properties of barium titanate. Attached Figure Description

[0023] Figure 1 This is a process flow diagram of the two-stage hydrolysis method for preparing nano-barium titanate powder according to the present invention.

[0024] Figure 2 This is a scanning electron microscope image of the barium titanate nanoparticles prepared in Example 3 of the present invention. Detailed Implementation

[0025] The present invention will be further illustrated below through specific embodiments and comparative examples. These embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention.

[0026] The core of the two-stage hydrolysis method for preparing nano-barium titanate powder provided by this invention lies in separating the hydrolysis process of the titanium source from the hydrolysis process of the hydrolyzing agent (such as dimethyl oxalate) in time. Combined with ultrasonic-assisted dispersion and a three-stage calcination process, this achieves controllable preparation of nano-sized barium titanate powder. The detailed operation of each step is described below.

[0027] S1, Ingredients Add pure water and anhydrous ethanol (volume ratio 1:1) to the reaction vessel and start low-speed stirring (to form a shallow vortex on the liquid surface) to ensure thorough mixing. This mixed solvent ensures good solubility of barium salt and rare earth salt, and also provides an appropriate amount of water for the hydrolysis of tetraethyl titanate added later. Then add a barium source (barium chloride, barium nitrate, barium carbonate, etc., preferably barium chloride) and all soluble rare earth salts (at least one of yttrium nitrate, dysprosium nitrate, and holmium nitrate), and continue stirring at low speed until completely dissolved, achieving uniform molecular-level dispersion of barium ions and rare earth ions in the solution. After the solid has completely dissolved, add an appropriate amount of hydrochloric acid to adjust the pH of the solution to 1.5–2.0.

[0028] The reaction vessel is placed in a chiller, and the ice-water bath temperature is controlled at approximately 5°C to maintain the internal solution temperature of the reaction system below 10°C. The stirring speed is increased to medium speed to create a deep vortex on the liquid surface. The titanium source (optionally titanium tetrachloride, titanium oxysulfate, tetraethyl titanate, tetraisopropyl titanate, etc., preferably tetraethyl titanate) is pre-diluted with anhydrous ethanol to a concentration of 5-10 wt% to form a titanium source-ethanol solution. Under ice-water bath conditions, the titanium source-ethanol solution is slowly added dropwise to the above solution while maintaining medium speed stirring until uniformly dissolved, obtaining a precursor mixture.

[0029] In the above operations, adjusting the pH value to 1.5–2.0 with hydrochloric acid aims to inhibit the hydrolysis reaction of the titanium source under acidic conditions, thus ensuring that the titanium source does not prematurely hydrolyze excessively during subsequent dropwise addition. If the pH value is too high, the titanium source will undergo violent hydrolysis during dropwise addition, generating uneven TiO2 particles and affecting the particle size distribution of the final product. Using an ice-water bath to control the solution temperature below 10°C further suppresses the hydrolysis rate of the titanium source. Since the hydrolysis of the titanium source is an endothermic reaction, the hydrolysis rate is extremely slow at low temperatures, ensuring that the titanium source is uniformly dispersed in the solution in a molecular state during dropwise addition and mixing, rather than precipitating locally as hydrolysis products. Medium-speed stirring creates a deep vortex on the liquid surface, ensuring that the droplets are quickly entrained into the bulk solution during the dropwise addition of the titanium source-ethanol solution, avoiding excessively high local concentrations. The titanium source is sensitive to water; if added directly to a large amount of water, it will rapidly hydrolyze to form a precipitate. Therefore, it needs to be pre-prepared as an ethanol solution and added slowly to control its contact rate with water. The order in which the titanium source is added is crucial. It must be done after the barium source and rare earth salt have completely dissolved and under ice-water bath conditions. If the titanium source is added at room temperature, or if the titanium source is added before the barium salt, the titanium source will hydrolyze prematurely, thus compromising the controllability of the subsequent two hydrolysis stages.

[0030] S2, First hydrolysis stage The precursor mixture obtained in step S1 was heated while the stirring speed was reduced to a low speed (liquid swirls were visible on the surface, with shallow vortices), and ultrasonic treatment was initiated (frequency 20–40 kHz). The mixture was heated to 35–40 °C and held at this temperature for 2–3 hours. Upon reaching 35–40 °C, the hydrolysis rate of tetraethyl titanate significantly increased. During the 2–3 hour holding period, tetraethyl titanate reacted with water to produce titanium hydroxide / hydrated titanium oxide (Ti(OH)4 / TiO2·nH2O) and ethanol, as shown in the following reaction equation: Ti(OC2H5)4 + 4H2O → Ti(OH)4 / TiO2·nH2O + 4C2H5OH (ethanol) The reaction product Ti(OH)4 / TiO2·nH2O was uniformly dispersed in the solution in colloidal form. The solution showed a very pale blue color, which is a typical optical characteristic of nanocolloids, indicating that the hydrolysis products have reached the nanoscale and are uniformly dispersed.

[0031] After heating to the predetermined temperature, stop stirring and turn on medium-speed stirring for 1 minute every 1-2 hours (for reaction vessels designed with a material self-circulation device, self-circulation can be turned on to promote material homogenization). During the heat preservation process, minimize mechanical disturbance to the nucleation and growth of colloidal particles, allowing the hydrolysis reaction to proceed smoothly under relatively static conditions, which is beneficial for forming colloidal particles with uniform particle size. The role of ultrasonic treatment in this stage is twofold: firstly, the microjets and shock waves generated by ultrasonic cavitation can promote sufficient contact between tetraethyl titanate and water molecules, enhancing the mass transfer process of the hydrolysis reaction; secondly, the cavitation effect can effectively break up any soft agglomerates that may form between colloidal particles, ensuring that the hydrolysis products exist in the form of monodisperse nanocolloids. The heat preservation time (2-3 hours) and temperature (35-40℃) in this step need to be precisely controlled. If the time is too short, the titanium source will not be fully hydrolyzed, and some titanium source will still exist in a molecular state; if the time is too long or the temperature is too high, the colloidal particles may further agglomerate and grow. The reaction solution turning into a very pale blue gel indicates that hydrolysis is complete. After the incubation period, the first hydrolysis product is obtained.

[0032] S3, Second Hydrolysis Stage After the first hydrolysis stage is completed, while maintaining low-speed stirring and ultrasonic treatment, slowly add a hydrolyzing agent-ethanol solution (concentration of 20-30 wt%) to the first hydrolysis product. The hydrolyzing agent can be dimethyl sulfate, diethyl sulfate, dimethyl oxalate, dibutyl oxalate, urea, etc., preferably dimethyl oxalate. The addition rate of the hydrolyzing agent-ethanol solution should be slow (e.g., 50 ml / min) to inhibit or slow down the hydrolysis process and avoid excessively rapid precipitation due to excessively high local concentrations of the hydrolyzing agent. After the addition is complete, heat the system to 80-90°C and maintain this temperature for 4-8 hours, keeping the stirring low throughout the process.

[0033] Taking dimethyl oxalate as an example, the reaction process is explained. Dimethyl oxalate undergoes hydrolysis at 80–90°C to produce oxalic acid and methanol, as shown in the following reaction equation: C4H6O4 (DMO) + 2H2O → H2C2O4 (oxalic acid) + 2CH3OH (methanol) Immediately after oxalic acid is generated, it undergoes a complexation reaction with barium ions and Ti(OH)₄ / TiO₂·nH₂O in the solution to form barium oxalate precipitate (BaTiO(C₂O₂)₂·4H₂O), as shown in the following reaction formula: Ti(OH)4 + BaCl2 + 2H2C2O4 (oxalic acid) → BaTiO(C2O4)2·4H2O↓ + 2HCl Incubate at this temperature for 4–8 hours to ensure complete hydrolysis and complexation precipitation of dimethyl oxalate. The reaction solution changes from a blue gel to a white slurry, indicating that barium titanium oxalate precipitate has formed. After the incubation period, the second hydrolysis product is obtained.

[0034] It should be noted that the hydrolysing agent can only be added in the second stage. This invention uses dimethyl oxalate as an example to explain why. If dimethyl oxalate is added in the first stage (i.e., the titanium source hydrolysis stage), the titanium source hydrolysis reaction and the dimethyl oxalate hydrolysis reaction will occur simultaneously, which will cause the following serious problems: First, the Ti(OH)4 colloid produced by titanium source hydrolysis and the oxalic acid produced by dimethyl oxalate hydrolysis will undergo a complexation precipitation reaction at the same time. The mutual interference of the two reactions makes the nucleation process uncontrollable. In some areas, the oxalic acid concentration is too high, resulting in rapid precipitation, while in some areas, the oxalic acid concentration is insufficient, resulting in incomplete precipitation. The final product has a wide particle size distribution. Second, oxalic acid is an acidic substance, and its presence will change the pH value of the system. The hydrolysis rate of the titanium source is highly sensitive to the pH value, and the change in pH value will further interfere with the consistency of titanium source hydrolysis. Third, when the two reactions occur simultaneously, byproducts such as ethanol and methanol produced by hydrolysis will accumulate in the system, affecting the mass transfer efficiency of subsequent reactions. Therefore, the hydrolysis process of the titanium source must be separated from the hydrolysis process of dimethyl oxalate in time. That is, the titanium source should be completely hydrolyzed under optimized conditions to form a uniform colloidal dispersion system first, and then dimethyl oxalate should be introduced for in-situ hydrolysis and precipitation. Only in this way can the precipitation reaction be carried out simultaneously in a uniform system.

[0035] Ultrasonic treatment plays a crucial role in this stage. During the complexation precipitation reaction, the strong shear force generated by ultrasonic cavitation effectively breaks up soft agglomerates between precipitate particles, preventing them from immediately agglomerating after formation. Simultaneously, the mechanical agitation of ultrasound enhances the uniform diffusion of the precipitate produced by the hydrolysate in the system, avoiding localized supersaturation. The hydrolysate must be pre-prepared as an ethanol solution and added slowly; directly adding a solid hydrolysate or rapidly adding its solution will result in excessively high local concentrations, leading to the production of large amounts of precipitate, excessively high local supersaturation, excessively fast precipitation rates, and uneven particle size. For example, directly adding solid diethyl oxalate or rapidly adding its solution will also result in excessively high local concentrations, producing large amounts of oxalic acid, leading to excessively high local supersaturation, excessively fast precipitation rates, and uneven particle size. A holding time of 4–8 hours ensures complete reaction.

[0036] S4, Washing After the second hydrolysis stage is completed, the heating is turned off, and the second hydrolysis product is allowed to cool to room temperature before being passed into a circulating filtration device for washing. The filter membrane used in the circulating filtration device can be any one of a honeycomb tubular ceramic membrane, a disc-type rotating ceramic membrane, or a flat-plate ceramic membrane, with a disc-type rotating ceramic membrane being preferred. Before washing, the material is filtered and concentrated to control the slurry solid content at 25±5% to improve washing efficiency and reduce the consumption of pure water. Concentrating the slurry solid content to 25±5% relatively increases the concentration of soluble impurities in the slurry, resulting in a larger concentration gradient and stronger mass transfer driving force during pure water washing, allowing the washing endpoint to be reached with less water and in a shorter time. Then, fresh pure water is continuously passed into the washing tank while continuous circulating filtration is performed to remove some of the Cl from the slurry. - Soluble impurities such as ions (from hydrochloric acid and barium chloride), methanol (from dimethyl oxalate hydrolysis), and ethanol (from titanium source-ethanol solution and hydrolysis agent-ethanol solution and solvent) are removed through washing. During the washing process, the conductivity of the waste liquid is sampled periodically at the washing outlet. Washing is considered complete when the conductivity of the transparent filtrate is ≤50 μS / cm. A conductivity ≤50 μS / cm is used as the endpoint of washing and is a reliable indicator based on extensive experimental verification. When the conductivity of the filtrate drops below this value, it indicates that the concentration of soluble ions in the slurry has decreased to an extremely low level, and the impact of residual impurities on the final powder properties is negligible.

[0037] S5, Drying The washed slurry is fed into a spray dryer for drying. The inlet air temperature for spray drying is 180–200℃, and the outlet air temperature is 80–90℃. Spray drying is a process of rapidly removing moisture from the slurry. Compared to traditional oven drying, spray drying has the following advantages: the slurry is atomized into tiny droplets in the spray dryer, and the moisture evaporates rapidly in the hot air, resulting in an extremely short drying time (on the order of seconds). This effectively prevents the particles from hardening and agglomerating due to capillary forces during the drying process. The parameters of 180–200℃ inlet air temperature and 80–90℃ outlet air temperature ensure rapid evaporation of moisture while avoiding premature decomposition of the precursor due to excessively high temperatures. An intermediate powder is obtained after drying.

[0038] S6. Calcination and sieving The intermediate powder obtained by spray drying is evenly placed in a calcination container (corundum crucible, zirconia crucible, mullite crucible, high-purity corundum crucible is preferred, which can balance costs and ensure powder purity) and placed in a calcination furnace for three-stage calcination.

[0039] Low-temperature calcination: The temperature is increased to 400–500℃ at a rate of 0.2–0.5℃ / min, and held for 6–8 hours to remove Cl. - Ions. Cl - Ions can volatilize from powder at relatively low temperatures; slow heating and long-term holding ensure the preservation of Cl. - Ions have ample time to diffuse from the interior of the powder to the surface and volatilize, avoiding the loss of Cl due to excessively rapid heating. - The ions are trapped inside the particles and cannot be removed.

[0040] Medium-temperature calcination: The temperature is increased to 600–700℃ at a rate of 0.2–0.5℃ / min and held for at least 6 hours to remove residual carbon (C) from the intermediate powder. The barium titanate precursor contains a large amount of organic components (oxalate), which decompose in the 600–700℃ temperature range, releasing carbon as CO / CO2. This stage also employs slow heating and long holding times to ensure complete decomposition of the organic components and thorough removal of carbon. Residual carbon will affect the purity and dielectric properties of the barium titanate powder.

[0041] High-temperature calcination: The temperature is rapidly increased to 900–1100℃ at a heating rate of 3–5℃ / min and held for 1 hour to complete the solid-state reaction of Ba and Ti to form BaTiO3. Within this temperature range, BaO from the barium source reacts with TiO2 from the dehydration of the titanium source hydrolysis products to form barium titanate crystals with a perovskite structure. The design purpose of rapid heating and short holding time is twofold: firstly, to provide sufficient energy for the solid-state reaction to proceed; and secondly, to shorten the high-temperature holding time, inhibiting excessive grain growth and ensuring that the product remains at the nanoscale.

[0042] Slow heating in the low-temperature and medium-temperature stages is crucial for ensuring complete impurity removal; if the heating rate is too fast, impurities will be sealed by the dense surface layer before they can diffuse out of the powder, resulting in residues. Rapid heating in the high-temperature stage inhibits grain growth while ensuring the reaction proceeds. The coordinated control of the three-stage calcination temperature range, heating and cooling rates, and holding time is the core guarantee for achieving high-purity, ultrafine barium titanate powder.

[0043] After calcination, the furnace is shut off to allow the powder to cool with the furnace. Once the powder has cooled to room temperature, it is removed and initially dispersed using an air jet mill, followed by sieving through a 300-mesh vibrating screen to obtain the finished nano-barium titanate powder. The combined use of the air jet mill and the 300-mesh vibrating screen can disperse any small amount of soft agglomerates that may form during calcination, and sieving ensures the uniformity of the final product's particle size.

[0044] There is a strict logical order between the steps of this invention, which cannot be arbitrarily changed. The specific analysis is as follows: (1) S1 must be before S2. In the batching step, the barium source and rare earth salt are mixed with the titanium source-ethanol solution under acidic and low temperature conditions to form a uniform precursor mixture. If the batching step is skipped and hydrolysis is carried out directly, the raw materials cannot be uniformly mixed at the molecular level, and the stoichiometric ratio of the subsequent hydrolysis and precipitation products will deviate significantly from the target value. (2) S2 must be before S3. This is the core innovation of this invention. The titanium source must be hydrolyzed first under optimized conditions (35-40℃, pH 1.5-2.0) to form a stable colloidal dispersion system before the hydrolyzing agent-ethanol solution can be added for precipitation. If the hydrolyzing agent is added first and then the titanium source is hydrolyzed, the titanium source hydrolysis reaction and the hydrolyzing agent hydrolysis reaction will proceed simultaneously, the nucleation process will be uncontrollable, and the product particle size distribution will be wide and encapsulate impurities. Therefore, S2 must be before S3, and the order cannot be changed. (3) S4 must be before S5. The purpose of washing is to remove soluble impurities. If drying is done before washing, the impurities will crystallize out with the evaporation of water and remain in the powder, which cannot be removed by subsequent washing. (4) S5 must be before S6. Spray drying transforms the slurry into a fluffy intermediate powder, which is beneficial for the diffusion of gas and the reaction during calcination. If the wet slurry is directly calcined, the water will rapidly vaporize at high temperature, which may cause the powder to splash and the crucible to break. In addition, the presence of water will affect the uniformity of the calcination temperature. (5) The order of the three-stage calcination cannot be changed. Low temperature stage (except Cl) - The order of the temperature range (excluding C), intermediate temperature range, and high temperature range (BaTiO3 formation) is based on the thermal decomposition characteristics of the barium titanium oxalate precursor. If the high temperature is followed by the low temperature, the BaTiO3 crystal phase forms earlier, and the Cl- crystals encapsulated inside... -Carbon (C) elements cannot be removed; if the intermediate temperature stage is skipped and the high temperature stage is performed directly, the C elements will be trapped inside the grains before they can be removed. Therefore, the order of the three-stage calcination cannot be changed.

[0045] The technical solution of the present invention will be further described below with reference to specific embodiments and comparative examples. It should be noted that the main raw materials used in the various embodiments and comparative examples of the present invention are as follows: Tetraethyl titanate (TEOT): chemically pure, used as a titanium source; Barium chloride (BaCl2): analytical grade, used as a barium source; Yttrium nitrate (Y(NO3)3), dysprosium nitrate (Dy(NO3)3), holmium nitrate (Ho(NO3)3): analytical grade, as soluble rare earth salts; Dimethyl oxalate (DMO): chemically pure, used as a hydrolysis agent; Anhydrous ethanol: analytical grade, used as a solvent; Hydrochloric acid (HCl): analytical grade, used to adjust pH value; Pure water: deionized water or distilled water.

[0046] Example 1

[0047] Please refer to Figure 1 The two-stage hydrolysis method for preparing barium titanate nanoparticles provided in this embodiment specifically includes the following steps: S1. Ingredients: Add pure water and anhydrous ethanol (volume ratio 1:1) to the reaction vessel, mix at low speed, then add 525g of barium chloride, 2.8g of yttrium nitrate, 2.1g of dysprosium nitrate, and 1.4g of holmium nitrate. Continue stirring at low speed until completely dissolved, then add hydrochloric acid to adjust the pH of the solution to 1.8. Place the reaction vessel in a chiller to maintain a 5°C ice-water bath, control the solution temperature <10°C, increase the stirring speed to medium speed to form a deep vortex on the liquid surface, and slowly add 575g of tetraethyl titanate to the resulting solution in a 5wt% tetraethyl titanate-ethanol solution. Stir until homogeneous to obtain the precursor mixture. S2, First hydrolysis stage: Reduce the stirring speed to low speed, apply ultrasonic treatment at a frequency of 30kHz to the precursor mixture and heat to 35°C, keep warm for 2 hours; stop stirring after heating to 35°C, and turn on medium speed stirring for 1 minute every 1 hour during the heat preservation process; allow tetraethyl titanate to be fully hydrolyzed to obtain the first hydrolysis product; S3. Second hydrolysis stage: While maintaining low-speed stirring and ultrasonic treatment, slowly add a 20wt% dimethyl oxalate-ethanol solution (addition rate of 50ml / min) prepared from 595g of dimethyl oxalate to the first hydrolysis product, then raise the temperature to 90℃ and keep it at that temperature for 5 hours, maintaining low-speed stirring throughout the process; this allows dimethyl oxalate to hydrolyze to generate oxalic acid, which then undergoes a complexation precipitation reaction with Ti and Ba ions in the solution to obtain the second hydrolysis product; S4. Washing: The second hydrolysis product is concentrated to a solid content of 25±5%, and then washed with a disc-type rotating ceramic membrane to remove soluble impurities until the conductivity of the filtrate is ≤50μS / cm. S5. Drying: The washed slurry is fed into a spray dryer with an inlet air temperature of 180-200℃ and an outlet air temperature of 80-90℃. The intermediate powder is obtained by spray drying. S6. Calcination and sieving: The intermediate powder is placed in a corundum crucible and then placed in a calcination furnace. It is calcined at low temperature, medium temperature and high temperature in sequence at 400℃ for 6 hours (heating at 0.5℃ / min), 650℃ for 8 hours (heating at 0.5℃ / min) and 950℃ for 1 hour (heating at 5℃ / min). After cooling, it is dispersed by an air jet mill and then sieved through a 300-mesh vibrating screen to obtain 530g of nano barium titanate powder.

[0048] Example 2

[0049] The difference from Example 1 is that in step S2, the stirring speed is reduced to low speed, the precursor mixture is subjected to ultrasonic treatment at a frequency of 20-40kHz and heated to 35°C and kept warm for 4 hours; after heating to 35°C, stirring is stopped, and medium speed stirring is turned on for 1 minute every 1-2 hours during the warming process; tetraethyl titanate is fully hydrolyzed to obtain the first hydrolysis product.

[0050] Example 3

[0051] The difference from Example 2 is that in step S3, while maintaining low-speed stirring and ultrasonic treatment, 595g of a 20wt% dimethyl oxalate-ethanol solution (added at a rate of 50ml / min) prepared with dimethyl oxalate is slowly added to the first hydrolysis product, and then the temperature is raised to 90°C and kept at that temperature for 8 hours, while maintaining low-speed stirring throughout the process; this allows dimethyl oxalate to hydrolyze to generate oxalic acid, which then undergoes a complexation precipitation reaction with Ti and Ba ions in the solution to obtain the second hydrolysis product.

[0052] Comparative Example 1 The difference from Example 1 lies in the following two steps: S2, First hydrolysis stage: Reduce the stirring speed to low speed, cancel ultrasonic treatment, heat to 35°C, and keep warm for 2 hours; after heating to 35°C, stop stirring, and turn on medium speed stirring for 1 minute every 1-2 hours during the heat preservation process; to hydrolyze tetraethyl titanate and obtain the first hydrolysis product; S3. Second hydrolysis stage: Maintain low-speed stirring, cancel ultrasonic treatment, and slowly add 595g of a 20wt% dimethyl oxalate-ethanol solution (addition rate of 50ml / min) to the first hydrolysis product. Then raise the temperature to 90℃ and keep it at that temperature for 5 hours, maintaining low-speed stirring throughout the process. This allows dimethyl oxalate to hydrolyze and generate oxalic acid. The oxalic acid then undergoes a complexation precipitation reaction with Ti and Ba ions in the solution to obtain the second hydrolysis product.

[0053] Comparative Example 2 The difference from Example 1 lies in the following two steps: S2, First hydrolysis stage: Reduce the stirring speed to low speed, cancel ultrasonic treatment, heat to 35°C, and keep warm for 2 hours; after heating to 35°C, stop stirring, and turn on medium speed stirring for 1 minute every 1 to 2 hours during the warming process; to hydrolyze tetraethyl titanate and obtain the first hydrolysis product.

[0054] S3. Cancel the second hydrolysis stage: Maintain low-speed stirring, cancel ultrasonic treatment, and directly add a 10% concentration of oxalic acid solution to the first hydrolysis product for co-precipitation (replacing the slow addition of dimethyl oxalate-ethanol solution and the heating hydrolysis process).

[0055] Comparative Example 3 The difference from Example 1 lies in the following two steps: S2. Cancel the first hydrolysis stage: No heating and heat preservation hydrolysis is performed after the ingredients are prepared.

[0056] S3. Cancel the second hydrolysis stage: While stirring, add a 10% concentration of oxalic acid solution directly to the precursor mixture for co-precipitation (replacing the entire hydrolysis and precipitation reaction process).

[0057] The powders obtained from the above embodiments and comparative examples were subjected to the following performance tests, and the test results were analyzed.

[0058] (1) Particle size test (D50, D90): The particle size distribution of the powder was tested using a laser particle size analyzer. A small amount of barium titanate powder was added to pure water, along with an appropriate amount of dispersant. After ultrasonic dispersion, the powder was tested on the analyzer, and the values ​​of D50 (the particle size corresponding to 50% of the cumulative distribution) and D90 (the particle size corresponding to 90% of the cumulative distribution) were recorded. D50 represents the average particle size of the powder, and D90 represents the large particle size of the powder. The difference between D90 and D50 can reflect the breadth of the particle size distribution.

[0059] (2) Specific Surface Area Test (BET): A specific surface area analyzer was used with nitrogen as the adsorbate. The nitrogen adsorption-desorption isotherm of the powder was measured at liquid nitrogen temperature (77K). The specific surface area of ​​the powder was calculated using the BET multilayer adsorption theory. Specific surface area is inversely proportional to the particle size of the powder; the smaller the particle size, the larger the specific surface area. For nano-barium titanate powder, specific surface area is a key indicator reflecting the fineness of the powder.

[0060] The particle size and specific surface area test results of the barium titanate powders prepared in each embodiment and comparative example are shown in Table 1 below.

[0061] Table 1. Test results of particle size and specific surface area of ​​barium titanate powder prepared in each example and comparative example.

[0062] Based on Table 1 Figure 2 It can be seen that: (1) The D50 values ​​of Examples 1 to 3 are 37 nm, 51 nm, and 64 nm, respectively, all ≤100 nm, which meets the requirements of high-end MLCCs for barium titanate powder particle size. The D90 values ​​are 92 nm, 96 nm, and 115 nm, respectively, with narrow particle size distribution. The BET values ​​are 26.1, 24.6, and 23.7 nm, respectively. 2 The / g indicates that the powder has a large specific surface area, further verifying its nanoscale characteristics. Example 1 (first hydrolysis 2 hours, second hydrolysis 5 hours) showed the smallest particle size (37 nm) and narrowest distribution (D90-D50=55 nm), indicating that the balance between nucleation and growth was optimal under these process conditions. Example 2 (first hydrolysis 4 hours) showed a slight increase in particle size (51 nm), indicating that the extended first hydrolysis time allowed for some growth of the colloidal particles. Example 3 (second hydrolysis 8 hours) showed a further increase in particle size (64 nm), indicating that the extended second hydrolysis time allowed for more growth time for the precipitated particles. The results of the three examples demonstrate that particle size can be effectively controlled by adjusting the hydrolysis time.

[0063] (2) In Comparative Example 1, the ultrasonic-assisted treatment was removed, and D50 increased to 98 nm, D90 increased to 285 nm, the particle size distribution became significantly wider (D90-D50=187 nm), and BET decreased to 21.6 nm. 2 / g. This indicates that the cavitation effect of ultrasound has a significant effect on inhibiting particle agglomeration and promoting uniform dispersion. Without the assistance of ultrasound, the soft agglomeration between particles during hydrolysis and precipitation cannot be effectively broken, resulting in increased product particle size, wider distribution, and reduced specific surface area. (3) Comparative Example 2 eliminated the second hydrolysis stage and instead added oxalic acid solution directly after the first hydrolysis for precipitation. Its D50 increased to 103nm, D90 increased to 374nm, and BET decreased to 19.8nm. 2 / g, the performance is significantly inferior to that of Examples 1-3. More importantly, Comparative Example 2 exhibited abnormal phenomena during the washing process, with large fluctuations in the pH value of the slurry and repeated fluctuations in the conductivity of the filtrate after reaching 500 μS / cm. This indicates that when oxalic acid solution is directly added for precipitation, Ti-Ba-oxalic acid complexes of different sizes are rapidly formed. These complex particles encapsulate uncomplexed raw materials and rare earth ions. During the washing process, the encapsulated structure is gradually broken, and the uncomplexed ions inside are released into the slurry and filtered out, resulting in repeated fluctuations in conductivity and pH value. This phenomenon also causes waste of raw materials (some rare earth ions and barium ions are lost during washing after being encapsulated) and a decrease in powder performance. (4) Comparative Example 3 eliminated all hydrolysis stages and directly added oxalic acid solution for precipitation after batching. Its D50 is as high as 278 nm, D90 is as high as 526 nm, and BET is as low as 12.4 nm. 2 / g, which is the worst performing among all samples. This indicates that the direct precipitation step leads to the rapid nucleation, aggregation, and growth of barium and titanium ions in the material solution, with a large number of uncomplexed barium, titanium, and rare earth ions being encapsulated inside the particles. At the same time, under the complexation effect of excessive oxalic acid, a large number of aggregated and grown particles agglomerate again, forming even larger particles, which greatly increases the particle size of the slurry and makes the particle size distribution extremely uneven. Furthermore, the rare earth ions undergo uneven aggregation, resulting in a significant decrease in powder performance. (5) In summary, the two-stage hydrolysis method for preparing nano-barium titanate powder provided by this invention can prepare high-quality nano-barium titanate powder with an average particle size ≤100nm, narrow particle size distribution, and large specific surface area through the time separation of titanium source hydrolysis and dimethyl oxalate hydrolysis, ultrasonic-assisted dispersion, and the synergistic effect of the three-stage calcination process. The results of Comparative Examples 1 to 3, from the opposite perspective, verify the key role of ultrasonic assistance, the second hydrolysis stage, and the complete two-stage hydrolysis process in powder performance. The absence of any one of these steps will lead to an increase in powder particle size, a wider distribution, and a decrease in performance.

[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention in any way. All equivalent transformations or modifications made in accordance with the essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing barium titanate nanoparticles via a two-stage hydrolysis process, characterized in that, The main steps include the following: S1. Ingredients: Add pure water and anhydrous ethanol to the reaction vessel, stir and mix at low speed, then add barium source and soluble rare earth salt, continue stirring at low speed until completely dissolved, then add hydrochloric acid to adjust the pH of the solution to 1.5~2.0; place the reaction vessel in an ice-water bath to control the solution temperature to less than 10℃, increase the stirring speed to medium speed, slowly add titanium source-ethanol solution to the solution, stir evenly to obtain precursor mixture; S2, First hydrolysis stage: Reduce the stirring speed to low speed, apply ultrasonic treatment to the precursor mixture and heat to 35~40℃, keep warm for 2~3 hours to fully hydrolyze the titanium source and obtain the first hydrolysis product. S3. Second hydrolysis stage: While maintaining low-speed stirring and ultrasonic treatment, slowly add hydrolyzing agent-ethanol solution to the first hydrolysis product, then raise the temperature to 80~90℃ and keep it at that temperature for 4~8 hours to hydrolyze the hydrolyzing agent to generate a precipitant. The precipitant undergoes a complexation precipitation reaction with titanium ions and barium ions in the solution to obtain the second hydrolysis product. S4. Washing: After concentrating the second hydrolysis product, wash it through a circulating filtration device to remove residual soluble impurities until the conductivity of the filtrate is ≤50μS / cm. S5. Spray drying: The washed product is spray dried to obtain intermediate powder; S6. Calcination and sieving: The intermediate powder is placed in a calcination furnace for three-stage calcination. After cooling, the calcined powder is broken up and sieved to obtain nano barium titanate powder.

2. The method according to claim 1, characterized in that, In step S1, the barium source is barium chloride; The titanium source is tetraethyl titanate, and the concentration of the titanium source in the titanium source-ethanol solution is 5-10 wt%. The soluble rare earth salt is one or more of yttrium salt, dysprosium salt, and holmium salt. The amount of a single rare earth salt added is 0.2 to 1 mol of the titanium source material, and the total amount of rare earth salt added is 0.5 to 2 mol of the titanium source material.

3. The method according to claim 1, characterized in that, In steps S2 and S3, the frequency of ultrasonic treatment is 20~40kHz; In step S2, stop stirring after heating to 35~40℃, and turn on medium speed stirring for 1~5 minutes every 1~2 hours during the heat preservation process; In step S3, maintain low-speed stirring throughout the heat preservation process.

4. The method according to claim 1, characterized in that, In step S3, the hydrolysant is selected from any one of dimethyl sulfate, diethyl sulfate, dimethyl oxalate, dibutyl oxalate, and urea, and the concentration of the hydrolysant in the hydrolysant-ethanol solution is 20~30wt%.

5. The method according to claim 1, characterized in that, In step S4, the filter membrane used in the circulating filtration device is selected from any one of honeycomb tubular ceramic filter membrane, disc rotating ceramic filter membrane, and flat plate ceramic filter membrane; Before washing, the second hydrolysis product is concentrated to a solid content of 25±5% before washing.

6. The method according to claim 1, characterized in that, In step S6, the specific operation of the three-stage calcination is as follows: Low-temperature calcination: Increase the temperature to 400-500℃ at a rate of 0.2-0.5℃ / min and hold for 6-8 hours; Medium-temperature calcination: Increase the temperature to 600-700℃ at a rate of 0.2-0.5℃ / min and hold for at least 6 hours; High-temperature calcination: Increase the temperature to 900-1100℃ at a rate of 3-5℃ / min and hold for 1 hour.

7. The method according to claim 1, characterized in that, In step S6, the calcining furnace is any one of a lifting calcining furnace, a box-type calcining furnace, a tunnel-type calcining kiln, or a tube furnace; the calcining container is any one of a corundum crucible, a zirconia crucible, or a mullite crucible.

8. The method according to claim 1, characterized in that, In step S6, the dispersing and sieving are carried out using an air jet mill in conjunction with a 300-mesh vibrating screen.

9. The method according to claim 1, characterized in that, In step S5, the inlet air temperature of the spray dryer is 180~200℃, and the outlet air temperature is 80~90℃.

10. The method according to claim 1, characterized in that, The average particle size D50 of the obtained barium titanate nanoparticles is ≤100nm.